2010
DOI: 10.1016/j.jvs.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcomes with cryoplasty for lower extremity arterial occlusive disease

Abstract: Cryoplasty was used in patients with extensive disease and multiple prior interventions. Cryoplasty provided poor patency rates and poor relief from claudication at 1 year in this population. Overall, cryoplasty seems to be an expensive endovascular tool with marginal clinical improvement in our experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The rates of freedom from major amputation were 93.4% at six months and 85.2% at 12 months with the lowest rate in those with Rutherford category 4 ischemia (0%) and highest in those with Rutherford category 6 ischemia (40%). More recently, another large series from Schmieder et al 13 reported on 88 cryoplasty procedures performed in 71 patients included 35 procedures for the treatment of in-stent stenosis. They had 71% initial technical success in these procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of freedom from major amputation were 93.4% at six months and 85.2% at 12 months with the lowest rate in those with Rutherford category 4 ischemia (0%) and highest in those with Rutherford category 6 ischemia (40%). More recently, another large series from Schmieder et al 13 reported on 88 cryoplasty procedures performed in 71 patients included 35 procedures for the treatment of in-stent stenosis. They had 71% initial technical success in these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cryoplasty is an expensive modality associated with a nearly $1851.50 upcharge when compared with CBA, 13 thus making the application of this technology difficult to justify without evidence of clinical success.…”
Section: Discussionmentioning
confidence: 99%